Nobiletin Increased Cytotoxic Activity Of Doxorubicin On Mcf-7 Cells But Not On T47d Cells - Edy Meiyanto,; Adam Hermawan,; Sendy Junedi,; Aditya Fitriasari,; Ratna Asmah Susidarti, (International Journal of Phytomedicine, 2011)
Nobiletin, a citrus flavonoid, shows strong cytotoxic effect in several cancer cell lines. The aim of this research was to investigate cytotoxic activities of nobiletin alone and in combination with doxorubicin. Cell viability assay of nobiletin, doxorubicin, and combination treatments were carried out by using MTT assay. Apoptosis assay was done using double staining method using Ethidium Bromide-Acridine Orange. Cell cycle distribution was determined by flowcytometry FACS-Calibur and data was analyzed by using ModFit LT 3.0 program. Nobiletin (5, 10 and 15 µM) increased cytotoxic effect of doxorubicin compared with doxorubicin alone in MCF-7 cells but not in T47D cells. The strongest cytotoxic activity was showed by the combination of 200 nM doxorubicin and 15 µM nobiletin in MCF-7 cells. Single treatment of doxorubicin 200 nM, nobiletin 15 µM and their combination induced G2/M accumulation in MCF-7 cells. Combination of 15 µM and nobiletin 200 nM doxorubicin showed strong synergism on apoptosis induction of MCF-7 cells. Single treatment of nobiletin 15 µM and doxorubicin 7.5 nM induced T47D cell accumulation in G1 phase and G2/M phase respectively, while their combination induced accumulation of T47D cells in G2/M phase. Nobiletin is potentially to be developed as co-chemotherapeutic agent for breast cancer, while molecular mechanism need to be explored.